Teacher collegiality and commitment in high-and low-achieving secondary schools in Islamabad, Pakistan / Madiha Shah - Shah, Madiha (2012)
Abundant literature has suggested that teacher collegiality is the basis of good teamwork and high professionalism in schools. This study analyzed the impact of teachers’ collegiality on their organizational and professional commitment in public secondary schools in Islamabad, Pakistan. The study also examined the differences of teacher collegiality, organizational commitment, and professional commitment in high-achieving and low-achieving schools. The effects of teacher personal variables (e.g. gender, educational level, and professional experience) on teacher collegiality, organizational commitment, and professional commitment were also investigated. A teacher collegiality scale (TCS) was developed and tested using exploratory and confirmatory factor analytic techniques. The final Teacher Collegiality Scale (TCS) comprised seven dimensions, namely (1) Demonstrating Mutual Support and Trust, (2) Observing One Another Teaching, (3) Joint Planning and Assessment, (4) Sharing Ideas and Expertise, (5) Teaching Each Other, (6) Developing Curriculum Together, and (7) Sharing Resources. The instruments of organizational commitment and professional commitment were adapted from Meyer, Allen, and Smith (1993). The survey instrument, comprising the TCS and Commitment Scale was distributed to a sample of 364 public secondary school teachers in eight high-achieving and nine low-achieving schools located in Islamabad. Structural Equation Modeling (SEM) with AMOS 16.0 was used to assess the impact of teacher collegiality on teachers’ organizational and professional commitment. Latent Mean Structure Analysis was used to determine the differences in teacher collegiality, organizational commitment, and professional commitment between high-achieving and low-achieving school teachers. The effects of demographic variables on study main variables were analyzed using Multivariate Analysis of Variance (MANOVA). The analysis confirmed that teacher collegiality positively impacted organizational commitment and professional commitment among secondary school teachers in Pakistan. Multi-group SEM analysis did not support for the moderating effects of school type based on achievement. The differences in teacher collegiality and professional commitment were found to be statistically non-significant between high-achieving and low-achieving school teachers. However, organizational commitment among high-achieving school teachers was significantly higher than low-achieving school teachers. Teacher collegiality among female teachers was more evident than male teachers. Female teachers were also found to be more organizationally committed in Pakistani schools. However, gender was not correlated with teacher professional commitment. Teachers with higher educational qualifications and/or teachers with more professional experience perceived collegiality to be higher in their respective schools. Similarly, an increase in educational level and professional experience heightens teachers’ commitment towards their organization and profession. The results of this study offer numerous implications for theory, practice, and future research.